Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

A review of APC somatic mosaicism and specific APC variants - I1307K and promotor variants - Shira Shur; Anna K. Sommer; Andrew Latchford; Isabel Spier; Lior H. Katz (Familial Cancer, 2025)
In the majority of patients with a classical Familial Adenomatous Polyposis (FAP) a pathogenic APC germline variant is identified; usually these are truncating variants in the coding region of APC. However, there are some special circumstances in which FAP is not the result of a pathogenic heterozygous germline variant in APC (mosaicism) and tspecific APC variants which do not cause FAP (I1307K and promotor variants). This paper will discuss these three conditions. APC somatic (postzygotic) mosaicism can be identified in up to 50% of unexplained adenomatous polyposis cases. The ability to identify APC postzygotic mosaicism depends on the the detection method (today usually next-generation sequencing) and also the tissue being analysed (investigation of multiple colorectal adenomas is more sensitive than leukocyte DNA). Identifying mosaicism has important implications in terms of an individual’s management and managing risk in family members. The I1307K variant in APC is prevalent among Ashkenazi Jews (AJ) but can also be found in Sephardi Jews and individuals of non-Jewish descent. While this variant does not cause polyposis, it increases the risk of colorectal cancer (CRC) by 1.68-fold in AJ individuals. However, the link between the I1307K variant and CRC risk in non-AJ populations, is less well-established. Furthermore, its potential impact on other types of cancer remains unclear. Consequently, the classification of this variant, along with appropriate screening and surveillance recommendations, remains a subject of ongoing debate among leading medical and genetic organizations. Variants in the APC promotor 1B region cause the relatively newly described condition of gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS). It is said to have an isolated gastric phenotype, with neither duodenal, large bowel nor extra-intestinal manifestations. There are many uncertainties regarding this condition, it’s penetrance and management. Lack of clinical data and poor understanding of the natural history of the condition remain significant barriers to developing guidelines to manage this condition.

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis - Isabel Spier; Martin Kerick; Dmitriy Drichel; Sukanya Horpaopan; Janine Altmüller; Andreas Laner; Stefanie Holzapfel; Sophia Peters; Ronja Adam; Bixiao Zhao; Tim Becker; Richard P. Lifton; et al. (Familial Cancer, 2016)